Sources and Ways of Controlling Manufacturing Industrial Waste in the Northern Ghana - Atsu, A. M; Thwala, W. D.; Aigbavboa, C. O. (International Journal of Engineering and Management Research, 2021)
Manufacturing waste forms part of industrial waste which is also rooted in solid waste. In Ghana, the ruling government has a flagship project known as one district one factory (1d1f). Most of these factories that are established and yet to be established are manufacturing industries. No doubt that these industries will generate lots of waste which must be managed properly. Also, the more factories are built, the more waste will be created. The main purpose of this paper is to identify and try to control the exact sources of waste generation on the production line of manufacturing industries. The method used was literature review, and interview of industry players. From the literature review, it was found that several sources of waste have been established such as municipal sources of waste, medical/clinical sources, agriculture sources, end-of-life-of automobile, industrial sources of waste, construction/demolition sources, and electronic sources of waste (eschooltoday, 2020, amauomo and baird, 2016) whiles the results from the interview session revealed that the exact point on the manufacturing line of the industry, which can be termed as sources of waste are; at the beginning, and sometimes the end of the production line. Observation on the production line also confirmed the perception of the factory hands, that at the beginning, and the end. Once the sources are identified, it is possible to control it. In conclusion, it was revealed that factory hands do not make critical observation on the production line. They agreed that if the sources are identified and controlled, it will reduce the cost of production which will increase their profit margin. It is therefore recommended that manufacturing industries should take much interest in identifying the sources of waste creation on their production lines. Also, they should take measurement seriously when feeding raw materials into the production line.